1992
DOI: 10.1002/mus.880150510
|View full text |Cite
|
Sign up to set email alerts
|

The heart in becker muscular dystrophy, facioscapulohumeral dystrophy, and bethlem myopathy

Abstract: We report a study, assessing involvement of the heart in 33 familial cases of Becker muscular dystrophy (BMD), 31 familiar cases of facioscapulohumeral (FSH) dystrophy, and 27 familial cases of Bethlem myopathy. In the patients with BMD, correlations of myocardial involvement with age and extent of musculoskeletal involvement were made. We performed physical examination, chest x-ray, electrocardiographic (EKG), and echocardiographic examination on all patients, and continuous EKG Holter-monitoring in the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 34 publications
4
41
0
2
Order By: Relevance
“…In a cross-sectional study we conducted in 1980 it was shown that nearly half of patients had ECG changes and 15% had DCM [12]. Our findings have been confirmed by others [11,23,32,33,45].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In a cross-sectional study we conducted in 1980 it was shown that nearly half of patients had ECG changes and 15% had DCM [12]. Our findings have been confirmed by others [11,23,32,33,45].…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-four patients originating from nine kindreds agreed to be seen again. A clear Xlinked recessive mode of inheritance was found in seven kindreds [12]. In five of these families and in one of the two remaining families, a mutation was found.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations